A method for preparing a single crystal ternary precursor
During the preparation process of the precursor of ternary lithium-ion battery, the batch production process of oxygen morphology and independent nucleation is solved, and the electrical performance and industrialization of the battery are improved. Productivity.
Patent Information
- Application Number
- CN202211656558.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-12-22
AI Technical Summary
Among the existing ternary lithium-ion batteries, there are problems of crystal nucleus oxidation out of control and low production efficiency during the preparation of nickel-cobalt-manganese ternary precursors, which affects the electrical performance and industrial production of the battery.
A method of preparing single crystal ternary precursors is adopted. By introducing oxygen into the second co-precipitation reaction, the precursor morphology is regulated, and the batch production process of independent nucleation is adopted to control the growth of crystal nuclei and improve the product. consistency and productivity.
Quantitative control of the oxidation degree of ternary precursors is achieved, surface morphology is modified, sintering performance and electrical performance are improved, production process is simplified, and industrial production efficiency is improved.
Smart Images

Figure CN116199272B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ternary lithium-ion batteries, and in particular relates to a method for preparing a single crystal ternary precursor. Background Art
[0002] With the rapid development of new energy vehicles, ternary lithium-ion batteries are considered to be one of the most promising batteries due to their comprehensive advantages such as high energy density, good cycle performance and stable structure. As one of the key components of ternary lithium-ion batteries, nickel-cobalt-manganese ternary layered composite positive electrode materials are favored by people due to their high capacity, rate performance and good cycle performance.
[0003] As the key raw material of ternary layered composite cathode materials, nickel-cobalt-manganese ternary precursors largely determine the performance of ternary layered composite cathode materials. Their micromorphology, crystallinity, sphericity, particle size distribution, tap density and other indicators will affect their electrical properties. For example, if the surface of the precursor is too dense, it will affect the diffusion of lithium ions into the interior of the precursor during the sintering process, and the capacity of the cathode material will be affected; and although the loose and porous structure of the precursor is conducive to the diffusion of lithium ions and can obtain a higher capacity, it is easy to over-burn during the sintering process, causing structural collapse and affecting the material's cycle performance. Therefore, studying the preparation and performance of nickel-cobalt-manganese ternary precursors is particularly important for improving the electrical properties of ternary layered composite cathode materials. Summary of the invention
[0004] The present invention is based on the inventor's discovery and understanding of the following facts and problems:
[0005] The co-precipitation method is currently the mainstream process for preparing ternary precursors. The main process is to pass the nickel-cobalt-manganese mixed salt solution, precipitant and complexing agent into a high-speed stirring synthesis kettle at a certain flow rate. The nickel-cobalt-manganese ions undergo a homogeneous co-precipitation reaction in the synthesis kettle. During the reaction, nitrogen and other protective gases are introduced to prevent the metal elements from being oxidized during the synthesis process. At the same time, key conditions such as the system pH, total alkalinity, and reaction temperature are controlled to generate a ternary precursor with specific requirements.
[0006] For the nickel-cobalt-manganese ternary precursor, its morphology is easily affected by the valence state of the manganese element, so the micromorphology of the ternary precursor can be adjusted by oxidation.
[0007] In the related art, CN112456568A discloses a pre-oxidized ternary precursor for positive electrode materials and a preparation method thereof, wherein 0.1% to 1% by mass of tetraethylammonium hydroxide is added to an ammonia solution, and the pre-oxidized ternary precursor is obtained by low-temperature calcination. However, the tetraethylammonium hydroxide added in the production process is toxic, and the low-temperature calcination prolongs the production process, reduces the production efficiency, and is not conducive to industrial production. Therefore, it is necessary to improve the preparation method of the ternary precursor to effectively control the microscopic morphology of the ternary precursor.
[0008] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, an embodiment of the present invention proposes a method for preparing a single crystal ternary precursor, which can quantitatively control the degree of oxidation during the manufacturing process of the ternary precursor to achieve the purpose of accurately modifying the surface morphology and accurately controlling the size of the precursor primary particles (the spherical particles of the precursor are secondary particles, and the small particles with strips, needles or blocks on the surface of the secondary particles are called primary particles), and finally improve the sintering performance and electrical properties of the ternary precursor.
[0009] The method for preparing a single crystal ternary precursor according to an embodiment of the present invention comprises the following steps:
[0010] (1) preparing a nickel-cobalt-manganese metal mixed salt solution, adding the solution together with a precipitant and a complexing agent into a first reaction kettle containing a base liquid under the protection of an inert gas to perform a coprecipitation reaction to obtain a crystal slurry;
[0011] (2) adding the slurry obtained in step (1) into a second reaction kettle, and then adding the nickel-cobalt-manganese metal mixed salt solution, a precipitant and a complexing agent, and simultaneously introducing an oxygen-containing inert gas to carry out a coprecipitation reaction;
[0012] (3) When the material fills the second reactor, a concentrator is used for concentration treatment, and an oxygen-containing inert gas is continuously introduced to allow the average particle size of the material in the reactor to grow to a target value;
[0013] (4) subjecting the material in step (3) to solid-liquid separation, aging, washing and drying to obtain the precursor.
[0014] The advantages and technical effects brought by the method for preparing a single crystal ternary precursor in the embodiment of the present invention are as follows: 1. The method in the embodiment of the present invention only introduces oxygen during the second co-precipitation reaction, which can avoid the problem of uncontrolled oxidation of the crystal nuclei in the slurry preparation stage of the first precipitation reaction, and can regulate the precursor morphology through the oxidation effect of oxygen, so that the primary particles become thinner to a certain extent, and the secondary particles have a certain degree of porosity; 2. The method in the embodiment of the present invention adopts an intermittent production process with independent nucleation. In the first step, crystal nuclei of smaller size are prepared, and then quantitatively added to the reactor for growth reaction. This can effectively avoid the problems of serious material agglomeration and particle abnormality caused by uncontrolled crystal nuclei in the initial stage of the intermittent production process, thereby greatly improving the consistency of the product; 3. The method in the embodiment of the present invention is simple and easy to implement, and the first reactor can be continuously produced to provide crystal nuclei for multiple second reactors, thereby improving production efficiency and realizing industrial mass production.
[0015] In some embodiments, in step (1) and / or step (2), the precipitant includes at least one of NaOH and KOH; and / or the complexing agent includes at least one of ammonia water and ammonium sulfate.
[0016] In some embodiments, in step (1), the nickel-cobalt-manganese metal mixed salt solution is made of NiSO4, CoSO4, and MnSO4 solutions, and is prepared according to the molecular formula Ni x Co y Mn z (OH)2, wherein x+y+z=1, 0.5≤x<1.0, 0≤y≤0.3, 0≤x≤0.5; and / or the total concentration of the nickel-cobalt-manganese metal mixed salt solution is 0.5-2.5 mol / L; and / or the flow rate of the nickel-cobalt-manganese metal mixed salt solution added to the first reactor is 2.0-8.0 L / h.
[0017] In some embodiments, in step (1), the base liquid is an aqueous solution containing sodium hydroxide and ammonia water, with a pH of 8.5 to 12.5 and a total alkalinity of 5 to 15 g / L.
[0018] In some embodiments, in step (1), the average particle size of the particles in the slurry is 0.5 to 2.0 μm.
[0019] In some embodiments, in step (1) and / or step (2), the total alkalinity of the coprecipitation reaction is 3 to 12 g / L, and the pH is 8.5 to 12.5. Preferably, the pH of the coprecipitation reaction system in step (2) is 0.05 to 0.5 lower than the pH of the coprecipitation reaction system in step (1); and / or, in step (1) and / or step (2), the temperature of the coprecipitation reaction is 30 to 80° C., and the stirring speed is 400 to 800 r / min.
[0020] In some embodiments, in step (2), the flow rate of the metal mixed salt solution added to the second reactor is 1 to 10 L / h, and the total flow rate of the oxygen-containing inert gas is 0.5 to 5.0 m / h. 3 / h, the oxygen volume concentration does not exceed 21%.
[0021] In some embodiments, in the step (3), when the concentration treatment is performed, the stirring speed is reduced by 1 to 15 r / min after every 5 hours of reaction, and the pH of the system is reduced by 0.01 to 0.15, while the total alkalinity of the system is kept unchanged; and / or, the target particle size D50 is 2.0 to 10.0 μm, and the diameter distance PSD = (D90-D10) / D50 < 0.7.
[0022] The embodiment of the present invention also provides a single crystal ternary precursor, which is prepared by the above method.
[0023] The advantages and technical effects brought by the single crystal ternary precursor of the embodiment of the present invention are as follows: 1. In the embodiment of the present invention, the precursor has a narrow particle size distribution, high sphericity, no agglomeration, and no irregular particles; 2. In the embodiment of the present invention, the specific surface area of the precursor is 4 to 15 m 2 / g, tap density is 1.6~2.4g / cm 3 , with good electrical properties.
[0024] An embodiment of the present invention further provides a positive electrode material, comprising the above-mentioned single crystal ternary precursor.
[0025] The advantages and technical effects brought by the positive electrode material of the embodiment of the present invention, the positive electrode material in the embodiment of the present invention has all the technical features of the single crystal ternary precursor of the embodiment of the present invention, and therefore has all the advantages and technical effects brought by the single crystal ternary precursor of the embodiment of the present invention, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a SEM image of the precursor prepared in Example 1;
[0027] Figure 2 is a SEM image of the precursor prepared in Example 2;
[0028] Figure 3 is a SEM image of the precursor prepared in Example 3;
[0029] Figure 4 is a SEM image of the precursor prepared in Comparative Example 1;
[0030] Figure 5 is a SEM image of the precursor prepared in Comparative Example 2;
[0031] Figure 6 This is a SEM image of the positive electrode material prepared in Example 4. DETAILED DESCRIPTION
[0032] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0033] The present invention is described in detail below in conjunction with specific embodiments and drawings.
[0034] The embodiment of the present invention provides a method for preparing a single crystal ternary precursor, comprising the following steps:
[0035] (1) preparing a nickel-cobalt-manganese metal mixed salt solution, adding the solution together with a precipitant and a complexing agent into a first reaction kettle containing a base liquid under the protection of an inert gas to perform a coprecipitation reaction to obtain a crystal slurry;
[0036] (2) adding the slurry obtained in step (1) into a second reaction kettle, and then adding the nickel-cobalt-manganese metal mixed salt solution, a precipitant and a complexing agent, and simultaneously introducing an oxygen-containing inert gas to carry out a coprecipitation reaction;
[0037] (3) When the material fills the second reactor, a concentrator is used for concentration treatment, and an oxygen-containing inert gas is continuously introduced to allow the average particle size of the material in the reactor to grow to a target value;
[0038] (4) subjecting the material in step (3) to solid-liquid separation, aging, washing and drying to obtain the precursor.
[0039] The method for preparing a single crystal ternary precursor in an embodiment of the present invention only introduces oxygen during the second precipitation reaction, which can avoid the problem of uncontrolled oxidation of the crystal nuclei in the slurry preparation stage of the first precipitation reaction, and can regulate the precursor morphology through the oxidizing effect of oxygen, so that the primary particles become thinner to a certain extent and the secondary particles have a certain degree of porosity; an intermittent production process with independent nucleation is adopted, in which smaller crystal nuclei are prepared in the first step, and then quantitatively added to the reactor for growth reaction, which can effectively avoid serious material agglomeration and particle deformity caused by uncontrolled crystal nuclei in the early stage of the intermittent production process, thereby greatly improving the consistency of the product; it is simple and easy to operate, and the first reactor can be continuously produced to provide crystal nuclei for multiple second reactors, thereby improving production efficiency and realizing industrial mass production.
[0040] In some embodiments, preferably, in step (1) and / or step (2), the precipitant includes at least one of NaOH and KOH; and / or the complexing agent includes at least one of ammonia water and ammonium sulfate. Further preferably, the concentration of the precipitant is 2 to 10.5 mol / L; the concentration of the complexing agent is 3 to 9 mol / L.
[0041] In the embodiments of the present invention, the types and concentrations of the precipitant and the complexing agent are further optimized to enable the coprecipitation reaction to occur quickly, thereby preparing densely structured crystal nuclei and subsequently growing into densely structured precursor particles.
[0042] In some embodiments, preferably, in step (1), the nickel-cobalt-manganese metal mixed salt solution is made of NiSO4, CoSO4, and MnSO4 solutions, and is prepared according to the molecular formula Ni x Co y Mn z (OH)2, wherein x+y+z=1, 0.5≤x<1.0, 0≤y≤0.3, 0≤x≤0.5; and / or, the total concentration of the nickel-cobalt-manganese metal mixed salt solution is 0.5-2.5 mol / L; and / or, the flow rate of the nickel-cobalt-manganese metal mixed salt solution added to the first reactor is 2.0-8.0 L / h. Further preferably, the concentrations of the NiSO4, CoSO4, and MnSO4 solutions are all 70-150 g / L.
[0043] In some embodiments, preferably, in step (1), the base liquid is an aqueous solution containing sodium hydroxide and ammonia, with a pH of 8.5 to 12.5 and a total alkalinity of 5 to 15 g / L. Further preferably, the volume of the base liquid is 40 to 90% of the total volume of the first reaction kettle.
[0044] In some embodiments, preferably, in the step (1), the average particle size of the particles in the slurry is 0.5 to 2.0 μm.
[0045] In the embodiment of the present invention, crystal nuclei with a particle size of 0.5 to 2 μm are first prepared, which can effectively avoid problems such as serious material agglomeration and particle abnormality caused by loss of control of crystal nuclei in the early stage of the reaction.
[0046] In some embodiments, preferably, in step (1) and / or step (2), the total alkalinity of the coprecipitation reaction is 3 to 12 g / L, and the pH is 8.5 to 12.5. Preferably, the pH of the coprecipitation reaction system in step (2) is 0.05 to 0.5 lower than the pH of the coprecipitation reaction system in step (1); and / or, in step (1) and / or step (2), the temperature of the coprecipitation reaction is 30 to 80°C, and the stirring speed is 400 to 800 r / min.
[0047] In some embodiments, preferably, in step (2), the flow rate of the nickel-cobalt-manganese metal mixed salt solution added to the second reactor is 1 to 10 L / h, and the total flow rate of the oxygen-containing inert gas is 0.5 to 5.0 m 3 / h, the oxygen volume concentration does not exceed 21%. Further preferably, the oxygen-containing inert gas is nitrogen containing air or oxygen.
[0048] In the embodiment of the present invention, by controlling the oxygen concentration in the gas, the oxidation degree of the precursor can be quantitatively controlled to achieve the purpose of accurately adjusting the size of the precursor primary particles and improving the electrical properties after sintering. If the oxygen content is too low, the precursor particles are densely stacked, which is not conducive to the diffusion of lithium during the sintering process, thereby affecting the positive electrode capacity of the lithium-ion battery; if the oxygen content is too high, the precursor is over-oxidized, the particles are loose and porous, the strength is reduced, and it is easy to break, thereby affecting the cycle and rate performance of the lithium-ion battery.
[0049] In some embodiments, preferably, in the step (3), when the concentration treatment is carried out, the stirring speed is reduced by 1 to 15 r / min after every 5 hours of reaction, and the pH of the system is reduced by 0.01 to 0.15, while the total alkalinity of the system is kept unchanged; and / or, the target particle size D50 is 2.0 to 10.0 μm, and the diameter distance PSD = (D90-D10) / D50 < 0.7.
[0050] In the embodiment of the present invention, the pH is adjusted by the DCS central control system, the alkalinity of the solution is determined by acid-base titration, and the flow rate of ammonia water is adjusted according to the titration result, so that the pH is slowly reduced and the total alkalinity remains unchanged; as the reaction proceeds, the solid content in the system will become higher and higher, the supersaturation of the system will increase, and there will be a strong nucleation tendency. The method of gradually reducing the rotation speed and pH can avoid secondary nucleation of the system and ensure the smooth growth of the precursor.
[0051] The embodiment of the present invention further provides a single crystal ternary precursor, which is prepared by the method of the embodiment of the present invention.
[0052] The single crystal ternary precursor of the embodiment of the present invention has a narrow particle size distribution, high sphericity, no agglomeration, and no irregular particles; the specific surface area of the precursor is 4 to 15 m 2 / g, tap density is 1.6~2.4g / cm 3 , with good electrical properties.
[0053] The embodiment of the present invention further provides a positive electrode material, comprising the single crystal ternary precursor of the embodiment of the present invention.
[0054] The advantages and technical effects brought by the positive electrode material of the embodiment of the present invention, the positive electrode material in the embodiment of the present invention has all the technical features of the single crystal ternary precursor of the embodiment of the present invention, and therefore has all the advantages and technical effects brought by the single crystal ternary precursor of the embodiment of the present invention, which will not be repeated here.
[0055] In some embodiments, preferably, the positive electrode material is obtained by mixing and sintering the precursor and a lithium salt. Further preferably, the lithium salt includes at least one of lithium carbonate and lithium hydroxide, and the ratio of the lithium salt to the precursor is 1.0:1 to 1.1:1; and / or, the sintering temperature is 600 to 900°C, the sintering time is 2 to 15 hours, and the sintering atmosphere is oxygen. More preferably, the concentration of the oxygen is 85 to 100%.
[0056] 1. Preparation method of precursor
[0057] Example 1
[0058] (1) preparing a mixed salt solution with a total metal concentration of 2 mol / L by mixing NiSO4, CoSO4 and MnSO4 solutions after extraction, separation and purification according to a metal molar ratio of 55:10:35; diluting a commercially available 32% sodium hydroxide solution into a 4.0 mol / L sodium hydroxide solution, and diluting a commercially available 25% ammonia water into an 8.0 mol / L ammonia solution;
[0059] (2) After 70 L of deionized water was introduced into the first reactor, sodium hydroxide solution was introduced to adjust the pH to 11.20, and then ammonia water was introduced to adjust the total alkalinity to 6.5 g / L; stirring was started at 650 r / min, and the reactor temperature was set to 55° C.;
[0060] (3) under a nitrogen protective atmosphere, a mixed salt solution, a sodium hydroxide solution and ammonia water are introduced into the first reaction kettle simultaneously by a metering pump, the flow rate of the mixed salt solution is controlled at 4.5 L / h, the flow rate of sodium hydroxide is adjusted by an online pH control system to maintain the pH at 11.20, the flow rate of ammonia water is adjusted by the total alkalinity, the total alkalinity is controlled at 5.5 g / L, the reaction is maintained until the particle size D50 stably reaches 1.5 μm, and then the reaction is stopped to obtain a slurry;
[0061] (4) 75 L of the above slurry was pumped into a second reactor with a total volume of 100 L using a peristaltic pump, and the stirring was turned on at 650 r / min. The reactor temperature was set to 55° C. At the same time, a mixed salt solution, sodium hydroxide solution and ammonia water were pumped in using a metering pump. The flow rate of the mixed salt solution was 6 L / h, and the reaction pH was maintained at 11.20. The total alkalinity of the reaction was kept unchanged at 6.5 g / L. At the same time, compressed air and nitrogen were introduced into the second reactor, and the flow rates of the two were adjusted so that the total flow rate was 1 m / h. 3 / h, oxygen volume concentration is 10%, and growth reaction is carried out;
[0062] (5) When the slurry fills the second reactor, the concentrator is turned on for concentration. Every 5 hours, the stirring speed is reduced by 5r / min, and the reaction pH is reduced by 0.03 until the particle size D50 grows to 3.8μm and the reaction is stopped. The obtained material is subjected to solid-liquid separation, aging, washing, and drying to obtain the precursor Ni 0.55 Co 0.10 Mn 0.35 (OH)2.
[0063] The precursor prepared in this example has a particle size of D50 = 3.78 μm and a diameter distance PSD = 0.64. The total reaction time is 62 h, and the solid content of the obtained precursor is 575 g / L and the specific surface area is 8.3 m 2 / g, tap density is 1.94g / cm 3 The SEM image of the precursor prepared in this example is as follows: Figure 1 As shown, it can be seen that the precursor primary particles are regular lath-shaped with an average size of 80*780nm.
[0064] Example 2
[0065] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (4), the oxygen volume concentration is 15% and the total reaction time is 55 h.
[0066] The precursor Ni prepared in this embodiment 0.55 Co 0.10 Mn 0.35 (OH)2, particle size D50 = 3.78 μm, diameter distance PSD = 0.64, solid content 518 g / L, specific surface area 9.7 m 2 / g, tap density is 1.91g / cm 3 The SEM image of the precursor prepared in this example is as follows: Figure 2 As shown, it can be seen that the primary particles are regular lath-shaped with an average size of 60*550nm.
[0067] Example 3
[0068] (1) preparing a mixed salt solution with a total metal concentration of 2 mol / L by mixing the purified NiSO4, CoSO4 and MnSO4 solutions after extraction and separation according to a metal molar ratio of 83:12:5; diluting a commercially available 32% sodium hydroxide solution into a 4.0 mol / L sodium hydroxide solution, and diluting a commercially available 25% ammonia water into an 8.0 mol / L ammonia solution;
[0069] (2) After 70 L of deionized water was introduced into the first reactor, sodium hydroxide solution was introduced to adjust the pH to 11.20, and then ammonia water was introduced to adjust the total alkalinity to 6.5 g / L; stirring was started at 650 r / min, and the reactor temperature was set to 70° C.;
[0070] (3) under a nitrogen protective atmosphere, a mixed salt solution, a sodium hydroxide solution and ammonia water are introduced into the first reaction kettle simultaneously by a metering pump, the flow rate of the mixed salt solution is controlled at 3.5 L / h, the flow rate of sodium hydroxide is adjusted by an online pH control system to maintain the pH at 11.45, the flow rate of ammonia water is adjusted by the total alkalinity, the total alkalinity is controlled at 4.0 g / L, the reaction is maintained until the particle size D50 stably reaches 1.7 μm, and then the reaction is stopped to obtain a slurry;
[0071] (4) 70 L of the above slurry was pumped into a second reactor with a total volume of 100 L using a peristaltic pump, and the stirring was turned on at 600 r / min. The reactor temperature was set to 70° C. At the same time, a mixed salt solution, sodium hydroxide solution and ammonia water were pumped in using a metering pump. The flow rate of the mixed salt solution was 3.5 L / h, and the reaction pH was maintained at 11.45. The total alkalinity of the reaction was kept unchanged at 4.0 g / L. At the same time, compressed air and nitrogen were introduced into the second reactor, and the flow rates of the two were adjusted so that the total flow rate was 1m 3 / h, oxygen volume concentration is 7%, and growth reaction is carried out;
[0072] (5) When the slurry fills the second reactor, the concentrator is turned on for concentration. Every 5 hours, the stirring speed is reduced by 5r / min, and the reaction pH is reduced by 0.03 until the particle size D50 grows to 3.8μm and the reaction is stopped. The obtained material is subjected to solid-liquid separation, aging, washing, drying and other operations to obtain the precursor Ni 0.55 Co 0.10 Mn 0.35 (OH)2.
[0073] The precursor prepared in the embodiment of the present invention has a particle size of D50=3.83 μm, a diameter distance of PSD=0.62, a reaction time of 68 h, a solid content of the obtained precursor of 560 g / L, and a specific surface area of 6.6 m 2 / g, tap density is 1.94g / cm 3 The SEM image of the precursor prepared in this example is as follows: Figure 3 As shown, it can be seen that the primary particles are regular lath-shaped with an average size of 160*620nm.
[0074] Comparative Example 1
[0075] The preparation method of this comparative example is the same as that of comparative example 1, except that in step (4), the volume concentration of oxygen is 0, that is, only nitrogen is introduced without compressed air, and the total reaction time is 68 h.
[0076] The precursor prepared in this comparative example has a particle size of D50 = 3.81 μm, a diameter distance of PSD = 0.65, a solid content of 623 g / L, and a specific surface area of 5.3 m 2 / g, tap density is 1.95g / cm 3 The SEM of the precursor obtained in this comparative example is as follows Figure 4 As shown, it can be seen that the primary particles are regular lath-shaped with an average size of 220*580nm, and the primary particles of the precursor that have not been oxidatively modified are obviously thicker than those that have been oxidatively modified.
[0077] Comparative Example 2
[0078] The preparation method of this comparative example is the same as that of comparative example 1, except that the oxygen volume concentration in step (4) is 21%, that is, only compressed air is introduced during the reaction without nitrogen, and the total reaction time is 49 hours.
[0079] The precursor obtained in this comparative example has a particle size of D50 = 3.79 μm, a diameter distance PSD = 0.72, a solid content of 469 g / L, and a specific surface area of 11.3 m 2 / g, tap density is 1.89g / cm 3 The SEM image of the precursor prepared in this comparative example is as follows: Figure 5 As shown in the figure, the microstructure is composed of fine strip particles with an average size of 35*320nm and larger strip particles with an average size of 150*800nm, and a small amount of hexagonal flake structure particles appear. The precursor that only introduces air is over-oxidized, the coprecipitation reaction is uncontrolled, and the microstructure is uneven, so that the precursor is composed of more than two primary particles of different sizes and shapes.
[0080] 2. Preparation method of lithium nickel cobalt manganese oxide positive electrode material
[0081] Example 4
[0082] Lithium carbonate and the precursor Ni 0.55 Co 0.10 Mn 0.35 (OH)2 was fully mixed in a ratio of 1.05:1 and sintered at 800°C for 12h in an atmosphere with an oxygen concentration of 90% to obtain the ternary positive electrode material LiNi 0.55 Co 0.10 Mn 0.35 O2, with lithium sheet as negative electrode, assembled into 2025 button cell and tested under 0.2 / 0.2C charge and discharge regime and 3.0-4.4V voltage.
[0083] Attached Figure 6 The SEM image of the prepared positive electrode material shows that after sintering, it presents an obvious single crystal structure. The test results are shown in Table 1 under the 0.2 / 0.2C charge and discharge system, and its capacity is 181.8mAh / g, and the first efficiency reaches 90.22%.
[0084] Example 5
[0085] The preparation method of the nickel cobalt manganese oxide positive electrode material of this embodiment is the same as that described in Example 4, except that the precursor used is the precursor prepared in Example 2. The test results are shown in Table 1 under the 0.2 / 0.2C charge and discharge system, and the capacity is 181.2 mAh / g, and the first efficiency reaches 89.93%, which is slightly lower than that of Example 4.
[0086] Example 6
[0087] The preparation method of the nickel-cobalt-manganese-lithium positive electrode material of this embodiment is the same as the method described in Example 4, except that the precursor used is the precursor prepared in Example 3 to prepare the ternary positive electrode material LiNi 0.85 Co 0.10 Mn 0.05 O2. The test results are shown in Table 1 under the 0.2 / 0.2C charge and discharge system. The capacity is 224.8 mAh / g and the first efficiency is 91.47%, which is better than that of Example 4 and Example 5. This is mainly due to the difference in the precursor composition.
[0088] Comparative Example 3
[0089] The preparation method of the nickel-cobalt-manganese-lithium positive electrode material of this comparative example is the same as the method described in Example 4, the only difference being that the precursor is the precursor prepared in Comparative Example 1, and is tested under a 0.2 / 0.2C charge and discharge regime. The results are shown in Table 1, with a capacity of 174.6 mAh / g and an initial efficiency of 88.6%, which are lower than the electrical properties of the positive electrode prepared by sintering the pre-oxidation-modified precursor, i.e., the precursor described in Examples 1 and 2.
[0090] Comparative Example 4
[0091] The preparation method of the nickel-cobalt-manganese-lithium positive electrode material in this comparative example is the same as the method described in Example 4, the only difference being that the precursor is the precursor prepared in Comparative Example 2, and is tested under a 0.2 / 0.2C charge and discharge regime. The results are shown in Table 1, with a capacity of 171.5 mAh / g and an initial efficiency of 85.3%, which are significantly lower than the electrical properties of the positive electrode prepared by sintering the pre-oxidation-modified precursor, i.e., the precursor described in Examples 1 and 2.
[0092] Table 1 Test results of electrical properties of positive electrode materials of Examples 4 to 6 and Comparative Examples 3 to 4
[0093] Charge and Discharge Example 4 Example 5 Example 6 Comparative Example 3 Comparative Example 4 0.2C / 0.2C(mAh / g) 181.8 181.2 224.8 174.6 171.5 First effect (%) 90.22 89.93 91.47 88.6 85.3
[0094] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0095] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A method for preparing a single crystal ternary precursor, characterized in that: The following steps are involved: (1) preparing a nickel-cobalt-manganese metal mixed salt solution, adding the solution together with a precipitant and a complexing agent into a first reaction kettle containing a base liquid under the protection of an inert gas, and performing a coprecipitation reaction to obtain a crystal slurry; (2) adding the slurry obtained in step (1) into a second reaction kettle, and then adding a nickel-cobalt-manganese metal mixed salt solution, a precipitant and a complexing agent, and simultaneously introducing an oxygen-containing inert gas to carry out a coprecipitation reaction; the flow rate of the nickel-cobalt-manganese metal mixed salt solution added to the second reaction kettle is 1-10 L / h, and the total flow rate of the oxygen-containing inert gas is 0.5-5.0 m / h. 3 / h, oxygen volume concentration is 7~15%; (3) When the material fills the second reactor, a concentrator is used for concentration treatment, and oxygen-containing inert gas is continuously introduced to grow the average particle size of the material in the reactor to the target value; when performing the concentration treatment, the stirring speed is reduced by 1-15 r / min after every 5 hours of reaction, and the pH of the system is reduced by 0.01-0.15, while the total alkalinity of the system is kept unchanged; (4) subjecting the material in step (3) to solid-liquid separation, aging, washing, and drying to obtain the precursor; In step (1), the base liquid is an aqueous solution containing sodium hydroxide and ammonia water, with a pH of 8.5-12.5 and a total alkalinity of 5-15 g / L; In the step (2), the total alkalinity of the coprecipitation reaction is 3-12 g / L, and the pH is 8.5-12.5; In the step (1) and / or the step (2), the temperature of the coprecipitation reaction is 30-80°C.
2. The method for preparing a single crystal ternary precursor according to claim 1, characterized in that: In step (1) and / or step (2), the precipitant includes at least one of NaOH and KOH; and / or the complexing agent includes at least one of ammonia water and ammonium sulfate.
3. The method for preparing a single crystal ternary precursor according to claim 1, characterized in that: In the step (1), the nickel-cobalt-manganese metal mixed salt solution is made of NiSO4, CoSO4, and MnSO4 solutions, and is prepared according to the molecular formula Ni x Co y Mn z (OH)2, wherein x+y+z=1, 0.5≤x<1.0, 0<y≤0.3, 0<x≤0.5; and / or the total concentration of the nickel-cobalt-manganese metal mixed salt solution is 0.5~2.5 mol / L; and / or the flow rate of the nickel-cobalt-manganese metal mixed salt solution added to the first reactor is 2.0~8.0 L / h.
4. The method for preparing a single crystal ternary precursor according to any one of claims 1 to 3, characterized in that: In the step (1), the average particle size of the particles in the slurry is 0.5-2.0 μm.
5. The method for preparing a highly single-crystal ternary precursor according to claim 1, characterized in that: In the step (1) and / or the step (2), the stirring speed of the coprecipitation reaction is 400-800 r / min.
6. The method for preparing a single crystal ternary precursor according to claim 1, characterized in that: In the step (3), the target particle size D50 is 3.78-10.0 μm, and the particle size distance PSD=(D90-D10) / D50<0.
7.
7. A single crystal ternary precursor, characterized in that: The method according to any one of claims 1 to 6 is used to prepare the product.
8. A positive electrode material, characterized in that Contains the single crystal ternary precursor as described in claim 7.
Citation Information
Patent Citations
Ternary material precursor preparation method and material prepared by ternary material precursor preparation method
CN113526569A
Nickel-cobalt-manganese ternary precursor and intermittent preparation process thereof
CN115385399A